2017
DOI: 10.1159/000480340
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of S100A8/A9-TLR4-NLRP3 Inflammasome Pathway in Contrast-Induced Acute Kidney Injury

Abstract: Background: Contrast-induced acute kidney injury (CIAKI) is a common cause of hospital-acquired acute kidney injury (AKI). S100A8/A9-TLR4-NLRP3 inflammasome pathway triggers inflammation, apoptosis and tissue injury in several AKI models. Nevertheless, the underlying mechanism of S100A8/A9-TLR4-NLRP3 inflammasome pathway in CIKAI is not clear. We aimed to investigate the possible role of S100A8/A9-TLR4-NLRP3 inflammasome in the pathophysiology of CIAKI. Methods: We treated male rats and NRK-52E cells by ioprom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 57 publications
5
54
1
Order By: Relevance
“…Additionally, it has been found that urine NGAL is significantly increased and related to the degree of albuminuria in type 2 diabetic nephropathy (T2DN) [21]. Besides, contrast-induced acute kidney injury (CIAKI) presented with elevations in plasma biomarker of NGAL 24 h after iopromide injection [22]. Furthermore, the infusion of macrophages that overexpressing NGAL was related to decreased kidney interstitial fibrosis and inflammation [23].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…Additionally, it has been found that urine NGAL is significantly increased and related to the degree of albuminuria in type 2 diabetic nephropathy (T2DN) [21]. Besides, contrast-induced acute kidney injury (CIAKI) presented with elevations in plasma biomarker of NGAL 24 h after iopromide injection [22]. Furthermore, the infusion of macrophages that overexpressing NGAL was related to decreased kidney interstitial fibrosis and inflammation [23].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…Recently, studies have shown that renal ischemia, direct nephrotoxicity, and oxidative stress are responsible for the pathogenesis of CI-AKI [7, 8]. Our previous study showed that free radical scavengers, such as pentoxifylline, could effectively reduce reactive oxygen species (ROS), protecting the kidney from iodinated contrast-induced injury [9].…”
Section: Introductionmentioning
confidence: 99%
“…Contrast-induced nephropathy (CIN) is a frequent complication. The incidence of CIN varies from 3% to 14% and can reach as high as 20% in patients with high risk [2, 3]. Recent evidence suggests that CIN can cause long-term decline in renal function, leading to increased mortality [4, 5].…”
Section: Introductionmentioning
confidence: 99%